(untitled) (Педагогіка вищої та середньої школи, 2008)
In article the essence and prominent features of speech development of children in conditions bilingvizm reveals, pedagogical conditions of the organisation of training of children of the Ukrainian language in a preschool educational institution with training Russian are defined.